Team of five : the presidents club in the age of Trump - Brower, Kate Andersen (Harper, an imprint of HarperCollinsPublishers, 2020)
"After serving the highest office of American government, five men--Jimmy Carter, the late George H. W. Bush, Bill Clinton, George W. Bush, and Barack Obama--became members of the world's most exclusive fraternity. In Team of five, Kate Andersen Brower reveals what life is like after the presidency, and she uncovers the complex relationships among these former presidents, and first ladies, in a nation that has been upended by the Oval Office's current, norm-breaking occupant, President Donald Trump. With an empathetic yet critical eye--and drawing on an Oval Office meeting with Donald Trump, first-hand testimony from the Carters, and interviews with top aides, friends, and family members of the former presidents--Brower takes us inside an exclusive world."--Dust jacket flap.